Benefits and dangers of the internet from the perspective of parents of primary school students - Velki, Tena (Array, 2020)
The aim of this study was to examine parents' perceptions of the online benefits and dangers that their children encounter. Ninety-six parents participated in the study (82.3% mothers and 17.7% fathers). Participants, parents of children attending primary school, filled out a questionnaire consisting of sociodemographic questions and a scale of attitudes about the benefits and dangers of electronic media (computers, the Internet and mobile phones). The results of the research showed that the frequency of the Internet use is related to the parents’ perception of the benefits and dangers of the Internet. It was found that the more often parents use the internet, the less danger they perceive, and more benefits, and vice versa, the less often they use the Internet, they perceive more dangers and fewer benefits. At the same time, the results showed that the level of parental education is not significantly related to their perception of the benefits or dangers that their children encounter on the Internet. By increasing awareness of this issue and examining the actual state, teachers can specifically educate children and also parents about the safe use of the Internet.